Putting Dreyfus into action : the European credit transfer system - Markowitsch, Jörg [Verfasser]; Becker, Matthias [Verfasser]; Spöttl, Georg [Verfasser]; Luomi-Messerer, Karin [Verfasser] (My University, 2008)
A couple of years ago the development of a European Credit Transfer System for Vocational Education and Training (ECVET) started. The European Commission together with the member states are working on it and several pilot projects have been initiated mainly within the Leonardo da Vinci Programme of the European Commission. The problem of transfer as well as a convincing transparency of vocational competencies has remained unsolved until now because no adequate model for the description of acquisition of competencies has yet been developed. This contribution illustrates a model using the Dreyfus/Dreyfus approach of acquisition of profiles in such a way that the levels of competency development are not applied to overall professional actions (as shown for pilots, nurses, teachers and others), but to smaller entities of professional profiles. While strongly taking into account work related tasks and contexts (objects, tools, work organisation) we define "groups of competencies" and apply Dreyfus’ ladder to these new entities. That means we are adopting Dreyfus’ model in two ways: (1) applying the model to groups of competencies (corresponding to specific core work profiles) instead of using it for overall competency profiles (corresponding to professionals/experts); (2) we make the model flexible and dynamic by not restricting it to a certain number of levels, but only defining the differences between levels." (ÖIBF, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Kompetenz; Qualifikation; Österreich; Europa